A inclusão do surdo no ensino da Física – estudo de caso no Ensino Médio em Salinópolis - Pará - FIGUEIREDO, Felipe Gabriel de Oliveira (2020)
Inclusive education being in the relationship of socio-political discussions as an intrinsic condition to a more just, egalitarian and democratic society and following the conjecture that scientific knowledge has a significant role in the construction of people's autonomy, this topic is addressed in this research, the inclusion of deaf students in Physics Education. Through this monograph, which has the character of a qualitative research, the aim was to investigate the resources and devices used in state high schools in the region of Salinópolis-PA, for the transmission of a teaching aimed at their effective knowledge and immersion. in science. Investigating data and statistics a priori in Brazil and a posteriori in the municipality highlighted by the IBGE was important to plead this research. Thus, we sought to use simple materials and active methodologies in order to present suggestions for didactic practices that would favor the participation of deaf students in Physics classes in the regular classroom and in the Specialized Educational Service (AEE), in order to achieve effective and meaningful learning. To carry out this case study in the municipality of Salinópolis / PA, with the help of the Physics Teacher, Newton's Laws theme and a small approach on Pressure were chosen. With the construction of a methodological follow-up through the use of specific sign-terms of Physics in Libras, use of software and experiments, both were based on the premise of something that addressed their daily lives and that made sense to students, with this purpose it was chosen the Laws of Movement. The results obtained were satisfactory in relation to the learning process. It allowed us to see that it is possible to teach and teach Physics in the perspective of including deaf students. So, this possibility is strongly linked when implementing teachers.